ISLAMIZATION AS A PARADIGMATIC DICHOTOMIC SOLUTION TO ISLAMIC EDUCATION “Critical Epistemic Review” - Yusdani (Rumah Riset Publisher, 2023)
The following article discusses the Islamization of science as a solution to the dichotomy of Islam and science in the world of Islamic education. In addition, it is hoped that with this Islamization project Muslims will gain progress and glory of civilization. However, the problem is, is this Islamization really a solution for the scientific world and Islamic education today? The discussion of this paper attempts to analyze the background, basic assumptions, and examples of the application of Islamization both from a conceptual and institutional perspective. At the same time, a critical analysis was also carried out on the controversy surrounding the Islamization of both the supporters and the critics. In general, There are two variants of the Islamization theory, namely the Islamization of the IIIT style in Virginia, United States of America, and the Islamization of al-Attas in Malaysia. An important finding of this article is that Islamization is a creative response and answer from Muslim scholars who are concerned about the decline and backwardness of Muslims in both the fields of science and technology development. However, on the other hand, as a solution offer, this Islamization has also given rise to a number of serious problems, among others, is Islamization being carried out for all sciences whether social sciences, humanities, or the exact sciences? And how? Likewise, is it the knowledge or the knowledge that is Islamized? It seems that these critical questions need attention from supporters of Islamization.